2004
DOI: 10.1051/0004-6361:20035786
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the optical counterpart to the X-ray pulsar SAX J2103.5+4545

Abstract: Abstract. We report optical and infrared photometric and spectroscopic observations that identify the counterpart to the 358.6-s X-ray transient pulsar SAX J2103.5+4545 with a moderately reddened V = 14.2 B0Ve star. This identification makes SAX J2103.5+4545 the Be/X-ray binary with the shortest orbital period known, P orb = 12.7 days. The amount of absorption to the system has been estimated to be A V = 4.2 ± 0.3, which for such an early-type star implies a distance of about 6.5 kpc. The optical spectra revea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 39 publications
9
57
1
Order By: Relevance
“…Although the number of optical observations of SAX J2103.5+4545 is scarce, the information available indicates a correlation between the long-term optical and X/γ-ray variability. The optical observations (August and September 2003) reported by Reig et al (2004) coincided with the transition to an X-ray faint state (see Fig. 8).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although the number of optical observations of SAX J2103.5+4545 is scarce, the information available indicates a correlation between the long-term optical and X/γ-ray variability. The optical observations (August and September 2003) reported by Reig et al (2004) coincided with the transition to an X-ray faint state (see Fig. 8).…”
Section: Discussionsupporting
confidence: 63%
“…Recently, Reig et al (2004) has reported the first optical and infrared observations of this system leading to the identification of the optical counterpart with a B0V star.…”
Section: Introductionmentioning
confidence: 99%
“…We observe that shortly before the disappearance of the disc and during the first instances of the formation of a new disc, the Hα line profile is symmetric and double peaked. None of the Be/X-ray binaries that have gone through disc-loss phases and for which there is a good optical follow-up coverage exhibited asymmetric profiles during the initial stages of disc formation: X Per in 1990 (Clark et al 2001), 4U 0115+63 in 1997 ) and in 2002 (Reig et al 2007), 1A 0535+262 in 1999 (Haigh et al 1999;Grundstrom et al 2007) and RX J0440.9+4431 in 2001 (Reig et al 2004). That is, the effects of the density perturbation do not show up until the disc is fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…5 in Grundstrom et al (2007) for 1A 0535+262. Only a lower limit, >2 R * , can be given for RX J0440.9+4431 (Reig et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The optical counterpart is a B0Ve star (V = 14.2) at a distance between 3.2 and 6.5 kpc (Baykal et al 2002;Reig et al 2004). Baykal et al (2002) found a correlation between spinup rate and X-ray flux during the 1999 outburst.…”
Section: Introductionmentioning
confidence: 99%